Pengembangan Bisnis Rintisan Berbahan Baku Daun Kelor dalam Berbagai Bidang Manajemen - Wijaya, Ferrymenatos; Jonina, Felicia; L’Haqeem, Harry; Effendi, Michelle Amadea; Angkiet, Richard; Anggreny, Tince; Fadhilah, Arief (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
Moringa leaves are raw materials that are going to be used as a product for a business with start-up status in Cipasung Village, Darma District, Kuningan Regency, West Java. In developing his business, Mr. Dian Nugraha as an owner of the business experienced various challenges in operational, marketing and financial aspects. The 2024 Community Development Program is here to help with this problem. The aim of carrying out the activity is to provide Mr Dian Nugraha with knowledge about areas of management that are challenges for him. This activity resulted in several things that were important for developing Mr Dian's business, such as Moringa leaf product innovation obtained through research and development of the raw materials, the creation of a logo and business name to establish a brand, and the making of structured financial records.